PERANCANGAN ICE COOL BOX MENGGUNAKAN BAHAN COMPOSITE (CBC) PADA KAPAL IKAN LAPIS FIBER 2 GT (GROSS TONNAGE) DALAM MASA KETAHANAN PANGAN DI MASA PANDEMI - Nazaruddin Nazaruddin; Muhammad Haiqal; Hendra Gunawan; Lulusi Lulusi; Akram Tamlicha; Iskandar Hasanuddin; Sarwo Edhy Sofyan; Syarifah Meurah Yuni; Ichsan Setiawan (Marine Kreatif, 2022)
Entering the economic era of free competition, various fishing technology supports have increased, but there are difficulties in terms of the availability of fish storage media in the long term. Products circulating today are not able to last long and are easily damaged. The problem that occurs is that the storage media does not have long durability against age, impact, maintenance and ease of repair. The composite material application applies the hand lay up method. The work process is carried out in stages starting from making patterns, molds to finished products. The material used consists of thermosetting resin, supported by reinforcing fiber consisting of E-glass fiber and organic ramie fiber. The combination of the two is called a hybrid material. The stages of this process are carried out efficiently and carefully until the final target is met for a quality Ice cool box product. Ice cool box composite as a direct application of campus research results so that it can be used for the needs of Acehnese fishermen.